2015
DOI: 10.1021/acs.chemmater.5b00288
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of the Persistent Luminescence of CaAl2O4:Eu,Nd

Abstract: CaAl2O4:Eu is a persistent luminescence (PL) material in the blue light region with potentially wide commercial applications. With the doping of Nd, the decay time can be elongated to more than 19 h. These excellent properties are believed to be in close relation with the electronic structures of the dopants, the defects, and the host material. In this work, we attempt to achieve a better understanding of the PL mechanism of CaAl2O4:Eu based on first-principles calculations. The electronic structures of the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(132 citation statements)
references
References 23 publications
4
128
0
Order By: Relevance
“…As we know, in luminescent materials, V O is usually a color center (or F-center). 34,39 In CaZnOS, V O can be formed with very low formation energy under the Zn-rich chemical limit. This F-center dominant fluorescence by V O with ÀU eff means that the emission is a two-electron process.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…As we know, in luminescent materials, V O is usually a color center (or F-center). 34,39 In CaZnOS, V O can be formed with very low formation energy under the Zn-rich chemical limit. This F-center dominant fluorescence by V O with ÀU eff means that the emission is a two-electron process.…”
Section: +mentioning
confidence: 99%
“…The exact inter-levels of activators and traps within the electronic structures suggested by theoretical study will provide a reference for the selection of such structures with optimal performance. 33,34,38,39 Therefore, it is necessary to open a preliminary discussion on the different native point defects in a potential UMPL to examine its energy conversion mechanism and to provide a useful reference for further experiments and various applications. 33,34,38,39 In this work, we discuss luminescence models covering the range from the typical oxygen vacancy (V O ) related F-center to other potential energy conversions through different optical transitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hussain [27] calculated the electronic structures of other common calcium aluminates, Ca 3 Al 2 O 6 , CaAl 2 O 4 , CaAl 4 O 7 , and CaAl 12 O 19 , by first principles based on the orthogonalized linear combination of atomic orbitals (OLCAO) method and found that their band gaps are 3.85, 4.16, 4.28, and 4.62 eV, respectively, which gradually increase with the increasing ratio of Al 2 O 3 . Qu et al [28] calculated the band structures of CaAl 2 O 4 using GGA–PBE, and the obtained band gap was 4.54 eV. The experimental band gap of CaAl 2 O 4 is likely between 5.8 and 6.7 eV.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] Recently, this approach was revealed as applicable for phosphors (an insulator in nature) as well, endowing them with PersL properties, [10][11][12][13][14][15] which opens up a brand-new perspective for exploring novel phosphorescent materials that are highly desirable in security signs, night displays, optical storage media, etc. [16][17][18][19][20] PersL is an interesting phenomenon whereby luminescence from an active center still lasts for a long period after ceasing the excitation. 16 However, there is some complex and profound physics behind the PersL mechanism, including excitation, delocalization, migration, storage, release, and recombination of charge carriers, which casts a veil of mystery over it.…”
Section: Introductionmentioning
confidence: 99%